IMPLEMENTATION OF IOT ON LOW POWER CONSUME SECURITY SURVEILLANCE SYSTEM WITH REAL-TIME ALERT - Agada, C. Victoria; Aligbe, Alex; Hafiz, Adeleke; Aiyudubie, Uyi S. (FUDMA JOURNAL OF SCIENCES, 2025)
The rate of security threat around the globe have been of the increase in recent time, the activities ranges from theft, kidnapping and among others. In cooperating image and video recorder on surveillance system can help to enhance the security system round the globe. Over the years, some researcher have carried out some researcher on security surveillance system by deploying motion detection, video and image recorders, application of Internet of Things (IoT) but much work have not be done on power consumption and real time alert system. This research work focuses on the development of an IoT based low power consume security surveillance system for real time monitoring and notification of footages. The surveillance system has the ability to provide real-time image of any criminal activities and send the information to the appropriate authorities without human interference.  The research work consists of an ESP32 Camera module, Passive Infrared (PIR) sensor, Arduino nano, servo motor, and a power supply from a Universal Serial Bus (USB) source for efficient and portable operation. From the results obtained from the research work, it shows that the developed security surveillance system is robust, energy-efficient, and cost effective with a motion detection false alarm of 3%, and response time for image capturing of 300ms and data transfer accuracy of 97.8%. This device is suitable in environment that required real-time monitoring and video recording in order to improve the security system in that location.
Keywords: Security; Image; Video recorder; ESP 32 Camera Module; Passive Infrared (PIR) sensor